2004
DOI: 10.1590/s1519-566x2004000300019
|View full text |Cite
|
Sign up to set email alerts
|

Foraging patterns of the leaf-cutter ant Atta laevigata (Smith) (Myrmicinae: Attini) in an area of cerrado vegetation

Abstract: Neotropical Entomology 33(3): 391-393 (2004) PALAVRAS-CHAVE: Especialização de microhabitats, herbivoria, limitação no forrageamento, Serra do CipóABSTRACT -Foraging rate can directly affect the impact that Atta laevigata (Smith) has on the environment. We attempted to assess the factors which most affect foraging rate of A. laevigata using data collected over a three month period in the Parque Nacional da Serra do Cipó in Minas Gerais, Brazil. A bimodal foraging pattern was observed on clear sunny days, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 2 publications
(3 reference statements)
1
9
0
2
Order By: Relevance
“…Second, our estimate of the average annual biomass consumption by an Atta colony is well within the range reported in similar studies conducted in other tropical habitats (Wirth et al 1997;Herz et al 2007). Finally, leaf-cutter ants are distributed throughout the Brazilian cerrado (Gonçalves 1960), and Atta nest density in our study site is within the range of values reported for other cerrado areas (2.7-6.0 nests per ha, Schoereder & Coutinho 1990;Viana et al 2004). The higher nest densities in the cerrado are probably why our estimates of biomass consumption by Atta spp.…”
Section: Fig 2 Relationship Between Nest Mound Size and Plant Biomasupporting
confidence: 82%
“…Second, our estimate of the average annual biomass consumption by an Atta colony is well within the range reported in similar studies conducted in other tropical habitats (Wirth et al 1997;Herz et al 2007). Finally, leaf-cutter ants are distributed throughout the Brazilian cerrado (Gonçalves 1960), and Atta nest density in our study site is within the range of values reported for other cerrado areas (2.7-6.0 nests per ha, Schoereder & Coutinho 1990;Viana et al 2004). The higher nest densities in the cerrado are probably why our estimates of biomass consumption by Atta spp.…”
Section: Fig 2 Relationship Between Nest Mound Size and Plant Biomasupporting
confidence: 82%
“…Previous surveys reported Atta colony densities in this savannah can be up to 22 times greater between locations, ranging from 0.6 to 13.3 nest/ha (Schoereder and Coutinho ; Schoereder ; Viana et al. ; Costa et al. ).…”
Section: Discussionmentioning
confidence: 82%
“…These differences are due to distinct methodological approaches because assessments included either incipient and young colonies (Schoereder and Coutinho ; Viana et al. ) or only mature ones (Schoereder ; Costa et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forrageamento em formigas é um processo complexo que envolve um sistema auto-organizável que pode ser estudado considerando o indivíduo, a colônia ou ambos (Schlindwein 2004). Alguns fatores podem modificar o comportamento de forrageamento das operárias como temperatura (Corrêa et al 2016), precipitação pluviométrica (Viana et al 2004), sazonalidade (Leal & Oliveira 2000, Lima et al 2006, Endringer 2011, tamanho do formigueiro (Moreira 1992), presença de parasitoides (Bragança et al 1998, Gazal et al 2007, queimadas (Araújo et al 2004), diferentes distâncias da planta ao ninho (Röschard & Roces 2003), diferentes tamanhos de carga (Cherrett 1972, Kleineidam et al 2007, Endringer et al 2012, plantas nocivas (Arenas & Roces 2016) e diferentes espécies de plantas podem ser cortadas e transportadas pelas operárias por diferentes estratégias de forrageamento (Endringer 2011(Endringer , 2015. Essa complexidade de fatores provavelmente contribui para que o forrageamento seja um comportamento flexível.…”
Section: Introductionunclassified